Anisometropia in School Going Children - Kanwal Zareen Abbasi,Qamar Farooq, Rashid Tufail,Ali Raza (Journal of Rawalpindi Medical College, 2016)
Background: To determine the frequency of anisometropia of ≥1.0D in children aged 05 to 15 years. Methods: In this cross sectional study, children aged between 5 and 15 years presenting with impaired vision were examined to diagnose the cause. Complete ocular examination was performed including retinoscopy for prescription of glasses. Cycloplegic refraction and post mydriatic test was done where indicated. Children, having refractive error as the sole cause of impaired vision, were included in the study and those having anisometropia of ≥1.0D were noted for result calculation. Results: The mean age of patients (n=100) was 9.56 + 6.0 years ranging from 5 to 15 years. There were 40 male and 60 female children. Considering the type of refractive error, 26% were myopes and 74% were hypermetropes. Anisometropia of ≥1.0D was seen in 9 out of 100 children with refractive error as the sole cause of impaired vision . There were 2 myopes in these 9 patients of anisometropia (20%) while remaining 7 were hypermetropes (78%). Conclusion: Hypermetropia is commoner than myopia (3:1) in the pediatric age group and females were showing a higher incidence of refractive errors than males (3:2). Anisometropia ≥1.0D (spherical/cylindrical) was more common among hypermetropes than myopes (78% vs 22%).Anisometropia exists in a significant number of school going children aged 05 to 15 years and needs to be dectected early and addressed timely to avoid the development of amblyopia and squint.